2016
DOI: 10.1002/pbc.26287
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive assessment of neuroblastoma minimal residual disease in ovarian tissue using RT‐qPCR—A strategy for improving the safety of fertility restoration

Abstract: These results are encouraging and offer hope in the near future for grafting ovarian tissue in women who survive cancer, whose fertility has been jeopardized by treatment, and who could benefit from OTC without oncological risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In these circumstances, patients are at risk of primary disease recurrence upon transplantation of ovarian tissue. In a study by Greze et al (2017), healthy ovarian tissue from 20 patients was in vitro contaminated with human NB cell lines and subsequently tested for minimal residual disease (MRD) with RT-qPCR for the relevant genes. The results showed PHOX2B (paired-like homeobox 2b) to be a reliable and sensitive marker of NB cells contaminating ovarian tissue, as it was able to detect as few as ten neoplastic cells present in the ovarian fragments.…”
Section: Neuroblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…In these circumstances, patients are at risk of primary disease recurrence upon transplantation of ovarian tissue. In a study by Greze et al (2017), healthy ovarian tissue from 20 patients was in vitro contaminated with human NB cell lines and subsequently tested for minimal residual disease (MRD) with RT-qPCR for the relevant genes. The results showed PHOX2B (paired-like homeobox 2b) to be a reliable and sensitive marker of NB cells contaminating ovarian tissue, as it was able to detect as few as ten neoplastic cells present in the ovarian fragments.…”
Section: Neuroblastomamentioning
confidence: 99%
“…The results showed PHOX2B (paired-like homeobox 2b) to be a reliable and sensitive marker of NB cells contaminating ovarian tissue, as it was able to detect as few as ten neoplastic cells present in the ovarian fragments. Cryopreserved ovarian tissue from two prepubertal patients with NB was also tested, but the PHOX2B gene was not detected by RT-qPCR, suggesting an absence of NB cells in these samples (Greze et al 2017).…”
Section: Neuroblastomamentioning
confidence: 99%
“…In addition, recent mapping of the neuroblastoma super-enhancer landscape demonstrated that a subset of neuroblastoma cells with adrenergic properties express PHOX2B , and that PHOX2B knockdown impairs these cells’ growth(Boeva et al 2017; van Groningen et al 2017). In clinical practice, PHOX2B positivity via immunohistochemistry can help distinguish neuroblastomas from other small round blue cell tumors, and PHOX2B mRNA expression offers a promising biomarker for the detection of minimal residual disease (Hung et al 2017; Greze, Brugnon, et al 2017; Greze, Kanold, et al 2017). However, given recent insights into the heterogeneity of cell types and differentiation states present within a given tumor, the absence of PHOX2B expression may not definitively exclude the presence of neuroblastoma.…”
Section: Familial Neuroblastomamentioning
confidence: 99%
“…One of several significant issues in ovarian tissue preservation is the risk of reseeding malignant cells that may cause reoccurrence of primary cancer [41]. A high risk of malignant cell reimplantation has been primarily observed in hematological malignancies [10,79,80], such as leukemia, Hodgkin lymphoma, and non-Hodgkin lymphoma [11]. Ovarian metastases have been additionally observed in gastric cancer (55.8%), colon cancer (26.6%), and lung cancer (23.4%) [81].…”
Section: Ovarian Tissue Cryopreservation and Reimplantationmentioning
confidence: 99%